DAKWAH POLITIK NABI MUHAMMAD SAW MELALUI SURAT KEPADA RAJA HERAKLIUS, KISRA ABRAWAIZ, MUQAUQIS, DAN NAJASYI - Nurul Insani, Agusti Alfi (Islamic Communication Journal, 2019)
Da'wah must be carried out using the right approach. Among the da'wah approaches is a political approach, called political da’wah. The practice of political da'wah has been exemplified by the Prophet Muhammad in the form of sending da'wah to rulers outside of Islamic rule. In this article, the author discusses the political da’wah of the Prophet Muhammad through a letter to four rulers, namely Heraclius, Kisra Abrawaiz, Muqauqis, and Najasyi. This study concluded that the Prophet Muhammad's political da'wah was a form of the head of state's political da'wah to the head of state. The da'wah method used is writing da'wah (da'wah bi al-qalam) through diplomacy strategies using letter media. Systematic of letters include the beginning of letters, letterhead, topic switching, contents of letters, and letterstamps. The Prophet Muhammad's letter contained an invitation to convert to Islam, good news (tabsyir), warning (tandzir), and also the verses of the Qur'an.